The incidence rate of Asymptomatic Bacteriuria among LIMU students - Alsahili, Ahmed (faculty of applied basic medical science - Libyan international medical university, 2022)
Asymptomatic bacteriuria(ASB ) is characterized as a 'UTI without clinical symptoms,' in which the person has significant growth of bacteria on their urine culture medium but no obvious signs of UTI. The incidence rate of asymptomatic bacteriuria is examined in this study among 24 male and female students at LIMU to see if there is a link between gender and Asymptomatic bacteriuria. Females are at a higher risk of having asymptomatic UTI when compared to males of the same age, according to research using urine samples. These findings point to a female susceptibility to UTI, which can be explained by a variety of reasons
Keywords: Bacteriuria